2021
DOI: 10.3389/fpsyg.2021.658599
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education Attitude of Adolescent Students in the Philippines: Importance of Curriculum and Teacher Sex and Behaviors

Abstract: The present study examined the attitudes of Filipino middle school students toward physical education (PE) and the associations between PE attitude and various personal and external correlates of PE. In total, 659 middle school students, aged between 12 and 19 years (M = 14.55; SD = 1.14), participated in the study. The Physical Education Attitude Scale (PEAS) was used to measure affective, cognitive, and motivational/behavioral attitudes of adolescent students toward PE. Results showed that middle school stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
(63 reference statements)
1
9
1
2
Order By: Relevance
“…Mean values from 4.13 to 4.51 obtained in our study are strongly positive and somewhat higher than results in previous studies (Cruz, Kim, & Kim, 2021;Orlić et al, 2017;Orlić, Mijatović, & Lazarević, 2018). Possible explanation could be that high school students are less involved in PE, than their primary school counterparts.…”
Section: Discussioncontrasting
confidence: 68%
“…Mean values from 4.13 to 4.51 obtained in our study are strongly positive and somewhat higher than results in previous studies (Cruz, Kim, & Kim, 2021;Orlić et al, 2017;Orlić, Mijatović, & Lazarević, 2018). Possible explanation could be that high school students are less involved in PE, than their primary school counterparts.…”
Section: Discussioncontrasting
confidence: 68%
“…Female physical education (PE) teachers are more prevalent among male middle school students, and male PE teachers are more prevalent among female middle school students. This study has provided a critical perspective that the school administrator must pay equal attention to the student-teacher relationship and the PE course curriculum setting (Cruz et al, 2021).…”
Section: Discussion Differences Between Male and Female College Stude...mentioning
confidence: 99%
“…In our study, we found that male university students’ PA was higher than that of females, consistent with the overall gender differences in PA in adolescence. A previous study showed that in exercise practice at the middle school stage, female physical education (PE) teachers were more popular with male students in middle school, and male PE teachers were more popular with female students ( Cruz et al, 2021 ). This investigation affirmed that we should pay attention to the course content, and create a good relationship between teachers and students in the PE curriculum.…”
Section: Discussionmentioning
confidence: 99%